CAD/CAM technologies in the surgical and prosthetic treatment of the edentulous patient with biomymetic individualized approach - POZZI, A. (CIC Edizioni Internationali, 2008)
BACKGROUND: The advent of modern endosseous implant design and improved surface technology has allowed the development of new restorative techniques that decrease patient’s total treatment time. Utilizing the latest scanning, CAD/CAM and manufacturing technolgies we are able to manufacture individualized dental restoration with high accuracy and a perfect precision of fit. MATERIALS AND METHODS: This report describes the rehabilitation of a completely edentulous patient utilizing a CT-based implant planning with computer-assisted surgical design, simultaneous CAD/CAM fabrication of a surgical template, a flapless surgical placement of the implants, and a prefabricated fixed complete denture for an immediately loaded restoration according to Nobel Biocare’s Teeth-in-an-Hour™ (Nobel Biocare Goteborg, Sweden) protocol. This systematic approach to full mouth rehabilitation reduces the time necessary for an edentulous patient to go from severely atrophic alveolar support to implant retained prosthetic restoration. These aspects of minimally invasive and simplified surgery, along with reducing the treatment time and postsurgical discomfort, are beneficial to the patient, and allowing for rehabilitation with the same level of success as in flap surgery. CONCLUSION: The Teeth-in-an-Hour protocol is a unique solution made possible by the Procera System. With the aid of the CT scans and a virtual planning software, a custom fabricated precision drill guide and a pre-manufactured prosthesis can be made before surgery. The execution of implant placement is performed with a flapless procedure that results in minimal surgical intervention. This results in a short and non-traumatic surgery with a minimum of postoperative complications, allowing the patient to leave the chair with a fixed prosthesis. Utilizing the latest scanning, CAD/CAM and manufacturing technologies the dental team is able to develop individualized zirconia full arch framework with high accuracy and precision of fit.